New species of the genus Thrissops (Teleostei, Ichthyodectiformes) in the Upper Jurassic of the Solnhofen-Archipelago (Germany) and Kimmeridge Clay (England) - Martin Ebert (Zitteliana)
Two new species of the poorly known genus Thrissops (Teleostei, Ichthyodectiformes) are described here in detail. Thrissops ettlingensis sp. nov. was recently found in the marine lower Tithonian Plattenkalk of Ettling (Bavaria, Germany), at the excavation site of the Jura-Museum Eichstätt, and Thrissops kimmeridgensis sp. nov. from the Kimmeridge Clay of the Dorset, England. Six adults and one juvenile of Th. ettlingensis in excellent preservation, some with stomach content and color pattern, were excavated in Ettling by the author. Of Th. kimmeridgensis more than 80 specimens were excavated and exceptionally prepared over the last years by Steve Etches. The characters of the skull, the positions and shape of the dorsal and anal fins and some features of the caudal skeleton strongly support the assignment of these fish to the order Ichthyodectiformes. The two new species belong to the genus Thrissops by morphological and skeletal features such as high body shape and short but high cranium. The genus Thrissops from the Upper Jurassic (Kimmeridgian/Tithonian) is among the first true Teleostei and belongs to the stratigraphically oldest Ichthyodectiformes (Middle Jurassic to Upper Cretaceous). It is the genus with the first larger predatory fish among the Teleostei; Th. ettlingensis still possessing some primitive features such as a comparably low number of abdominal vertebrae and low number of anal pterygiophores. Thrissops ettlingensis and Thrissops kimmeridgensis are here compared to the other known Upper Jurassic Thrissops species of the Solnhofen Archipelago (Germany), Cerin (France) and Dorset (England), and all other known Jurassic Ichthyodectiformes.